(untitled) (Research, Society and Development, 2020)
Adequate nutrition is one of the essential factors for healthy growth and development at all stages of life. Thus, school feeding aims to partially meet the nutritional needs of students and thus promote healthy eating in the school environment. The objective of this study is to evaluate the quality of school meals, through acceptability tests that are carried out directly with students. This is a systematic review. The following databases were used for data collection: electronic Scientific Eletronic Library Online (SCIELO), Latin American Caribbean Literature in Public Health (LILACS), US National Library of Medicine (PUBMED), Periodic Coordination for the Improvement of Higher Education Personnel (CAPES). After reading the articles, 11 duplicate articles were eliminated, of which 59 articles remained. Of these, 30 were excluded after reading the abstracts. Of the 29 eligible articles, 19 were excluded for the following reasons: insignificant sample, literature review, articles published more than ten years ago. Most of the studies analyzed obtained an acceptability index for school meals above 50%, but the majority did not reach 85% in the sum of the results expressed by the acceptability tests. However, when the acceptance is below this value, there is a reduction in food resources, inadequate planning of menus and types of preparations.